Sandhan Karma - Base of Ayurveda and Modern Sciences - A Review - Potalia, Pankaj; Gupta, Rajesh Kumar; sharma, Vishnu Dutt (International Research Journal of Ayurveda & Yoga, 2021)
As shown by Aacharya Sushruta, "Sandhan karma” is a very old technology that can be equated to plastic surgery or reconstructive surgery in modern times. However, pinpointing the exact date of the first reconstructive surgery on humans is difficult. Plastic surgery is one of the leading super speciality surgery fields. Many of the current science techniques are well established and yet adding greater precision is an ongoing endeavor to obtain perfection. If we compare these processes with those detailed by the Sushruta we know that most of them are followed the same way as Sushruta described them. Sushruta also acknowledges the modern literature on plastic surgery, which is a pioneer in plastic surgery for many operations. Autoplastic surgery, Cleft Lip procedures nowadays, had a direct origin from Sushruta Samhita, ranged from the fundamentals of plastic surgery to difficult procedures like rhino plastic. The evolution of cosmetic surgery is inextricably linked to ancient Indian surgical procedures. A serious endeavor has been made in this study to collect all accessible facts regarding Sandhan Karma and its relationship to the history and current age of plastic and reconstructive surgery. This article emphasizes a comparison of some of Sushruta Samhita and contemporary science fundamental concepts and practices of plastic surgery.